KEPUTUSAN PEMBELIAN PAKAIAN BATIK DITINJAU DARI KUALITAS PRODUK, PRODUCT ASSORTMENT, DAN STORE ATSMOSPHERE (Studi Pada Toko Batik Danar Hadi Surakarta) - Dhimas Wisnuaji Ikhsan; Bambang Mursito; Solichul Hadi (JURNAL ILMIAH EDUNOMIKA, 2020)
This research aims to study and explain the simultaneous and partial Product Quality, Various Products and Atsmosphere Stores on the Purchase Decision of Batik Clothing at the Batik Danar Hadi Store in Surakarta. This research method uses descriptive quantitative research design. The population is all batik consumers at the Surakarta Danar Hadi Batik Shop, which gets 100 consumers. The number of samples is all consumers of 100 respondents. Collecting data using a questionnaire. Data analysis techniques used statistical analysis are the coefficient of determination test, multiple linear regression test, F test, and t test. The results showed the product test, product quality, and store atmosphere simultaneously and significantly towards purchasing decisions at the Batik Danar Hadi Store in Surakarta. The results showed a positive and significant product quality on the buyer's decision at the Batik Danar Hadi Store in Surakarta. Product atsmosphere have a positive and significant influence on buyer’s decision at the Batik Danar Hadi Store in Surakarta. Store atmosphere has a positive and significant influence on buyer’s decision at the Batik Danar Hadi Store in Surakarta. Keywords: Purchasing Decisions, Variety of Products, Product Assortment and Store Atmosphere